Conservation of the rice bran for silage with different levels of hydration and addition of cornmeal Conservação do farelo de arroz integral por ensilagem com diferentes graus de hidratação e adição de fubá de milho - Tubin J.S.B.* (2016)
© 2016, Rev. Bras. Saúde Prod. Anim., Salvador.A study was carried out to evaluate the addition of cornmeal (FMI) at different hydration degrees to rice bran, as a strategy for its conservation by silage (FAR). Five relations of FAR and FMI were used: 10:0; 9:1; 8:2; 7:3 and 6:4, combined with five hydration levels: 10, 20, 30, 40 and 50% over initial weight, performing a 5x5 factorial design with four replications. In parallel, were prepared four similar silos only with FAR, without hydration (control silos). After 120 days of storage, the pH, titratable acidity, acidity index, fungi index, and water activity (Aw) were evaluated. The temperature (regarding to verify the aerobic stability) and the pH were determined at 24, 48 and 120 hour after opening. Interactions were observed for pH at opening time, titratable acidity, acid index and fungi index. No interactions were observed with Aw. The inclusion of 40% of cornmeal and 42.3% water improved the silage pH at opening and 43,6% improve the silage pH at 24 hours after opening. However, after 48 h of opening, all silages were inappropriate for consumption, the addition of cornmeal accelerated the deterioration of silage. Only on the control silos, the peroxidation process was observed. Then, the use of silage method for preserving the quality of rice bran was promising as a tool to reduce peroxidation independent of hydration level. We recommended for silage rice bran the inclusion of FMI 40% and 42.3% of water to optimize the pH in the opening.